2004
DOI: 10.1051/0004-6361:20041485
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric trajectories and light curves of shower meteors

Abstract: Abstract. Double station data on 496 meteors belonging to several meteor showers were obtained within the program of the video meteor observations during years 1998−2001. Analyzed meteors cover a range of photometric masses from 10to 10 −4 kg with a corresponding range of maximum brightness from +4.7 to −2.1 absolute magnitude. Atmospheric trajectories of Perseid, Orionid and Leonid meteors are analysed. These typical cometary high velocity meteors are compared to Geminid meteors with probable asteroidal origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
70
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 13 publications
16
70
0
Order By: Relevance
“…This is in agreement with the work done by Koten et al (2004) on several meteor showers (see their Fig. 3 on beginning heights versus photometric mass of fainter Perseid meteors).…”
Section: Meteoroid Strength and Densitysupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the work done by Koten et al (2004) on several meteor showers (see their Fig. 3 on beginning heights versus photometric mass of fainter Perseid meteors).…”
Section: Meteoroid Strength and Densitysupporting
confidence: 92%
“…For example, the beginning heights and lightcurve shapes of faint meteors show significant variation, while larger meteors vary in end height (Ceplecha et al 1998). Koten et al (2004) showed that the differences in lightcurves and beginning heights among major video meteor showers can be explained by differences in the chemical composition and physical structure of their parent bodies.…”
Section: Introductionmentioning
confidence: 99%
“…13, the iron meteoroids and the Na-free meteoroids started to ablate at lower heights than most meteoroids, while Fe-poor meteoroids started higher. Although Koten et al (2003Koten et al ( , 2004 found that the beginning height of cometary meteoroids also depends on the meteoroid mass, the dependence of the beginning height on the speed is sufficient for our purpose, and we can distinguish the variance of the material strength of different spectral classes of meteoroids.…”
Section: -Fe-poor Meteoroidsmentioning
confidence: 99%
“…Individual meteoroids are most likely irregular aggregates of dust grains. Small meteoroids often disintegrate into the constituents grains early during the atmospheric entry, producing meteors with nearly symmetrical light curves (Beech & Murray 2003;Koten et al 2004). …”
Section: Halley-type Cometsmentioning
confidence: 99%